The mitogenome of the brown pod-sucking bug Clavigralla tomentosicollis Stäl (Hemiptera: Coreidae) - Steele, L.D.; Sun, W.; Valero, M.C.; Ojo, J.A.; Seong, K.M.; Coates, B.S.; Margam, V.M.; Tamò, Manuele; Pittendrigh, Barry Robert (Elsevier, 2017)
The brown pod-sucking bug, Clavigralla tomentosicollis Stäl (Hemiptera: Coreidae), causes significant damage to cultivated cowpea, Vigna unguiculata Walp, a staple crop in sub-Saharan Africa. C. tomentosicollis pierce and suck sap from cowpea pods, resulting in reduced grain yield and quality. The complete, 16,089 bp mitogenome of C. tomentosicollis encodes 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and an A + T rich control region, with gene order and orientation identical to that of the insect ancestral gene order. The initiation and termination codons for the PCGs used standard ATN codons and TAA or TAG codons respectively. All predicted tRNAs fold into a clover-leaf secondary structures with the exception of tRNA-Ser (AGN) with a semi-loop dihydrouridine arm. The 1509 bps A + T rich region contains a single 89 bp tandem repeat unit duplicated 3.7 times. When compared with other published Coreoidea mitogenomes, C. tomentosicollis was also highly A − T skewed, and similar in both size and A − T%; however, its longer tandem repeat within the A + T rich region was unique. The C. tomentosicollis mitogenome can serve as a foundation to combine molecular marker data with pest monitoring strategies to better understand the population dynamics of this species.